Energy Efficiency, Carbon Intensity, and Green Economic Development in Indonesia: An Islamic Economics Perspective - Jonkenedi; Lucas Away, Johan; Ismayanti, Rika (Institut Agama Islam Negeri Kendari, 2026)
The transition toward a green economy has become increasingly important as countries seek to balance economic growth with environmental sustainability. Indonesia has demonstrated its commitment through the Net Zero Emission 2060 target, the expansion of renewable energy, and the development of green Islamic finance instruments. This study aims to examine the dynamic relationship among energy use, economic efficiency, and environmental performance within the framework of green economic development in Indonesia from an Islamic perspective. The study employs a quantitative time-series design using annual secondary data obtained from the World Development Indicators covering the period 2004–2023. Data were analyzed using the Vector Error Correction Model (VECM) to investigate both short-run and long-run relationships among variables. The findings indicate the existence of a significant long-run equilibrium relationship among energy use, economic efficiency, and carbon intensity. Environmental performance was found to play an important adjustment role in restoring equilibrium following short-term shocks. These findings support Green Growth Theory and are consistent with Islamic principles of stewardship, balance, and environmental responsibility. The study contributes to the development of sustainable economic policies and strengthens the integration of Islamic values into green economic development strategies.